CITRA TUBUH WANITA SEBAGAI SUMBER INSPIRASI KARYA SENI LUKIS - Vilanda, Avita Risqi; Suyasa, I Nyoman (Sanggitarupa, 2022)
This final project have to understand the image of woman’s body as a source of inspiration for painting. Through this final project I want the perfection of body appearance does not have standard but instead becomes a form of diversity. Difference in body shape, skin color, and body size should be things in human life that are generally accepted and not a form of problem such as standaration of beauty in society. In the process of creating this final project, the writer use the method of creation proposed by Hermann Von Helmholtz, which consists of, among others, saturation (data collect), incubation (precipitation) and illumination (Embodiment the work). Data collection is done through interview and take pictures directly to the relevant sources. The result of this final project show the idea of painting submit by the author is expect tobe a source of inspiration for many people, expecially woman, in responding to the acceptance of the diversity of body appearrences through the creation of body image beyond the standardization of society. Another way, by raising the topic of this woman body image, it is hope that people out there who feel they have shortcomings, especially in physical terms, become more accepting and respectful of themselves